Effect of supplementary pulsed LED light on lettuce growth under a greenhouse - Reyes-Rosas, Audberto; Moreno-Garza, Andrea Paola; Gomez-Ramirez, Emmanuel; Mounzer, Oussama; Khamkure, Sasirot; Lara-Viveros, Francisco M. (Revista Mexicana de Ciencias Agrícolas, 2025)
The intermittent LED light with short on/off pulses as a source of supplementary light to sunlight could promote greater vegetable growth with a consequent lower energy consumption; nevertheless, its effect on lettuce (Lactuca sativa L.) under greenhouse conditions has been little studied. The work evaluated how different regimes of pulsed LED light affect the photosynthetic rate, stomatal conductance, leaf area, and fresh and dry weight, considered plant growth parameters. These parameters were analyzed under a completely randomized experimental design, establishing five treatments, with a total of 8 plants grown per treatment, applying LED light on them as a source of supplementary light to sunlight at night. The results indicated that the pulsed LED light with short on/off periods (30/15 min) does not produce significant differences (Anova, p> 0.05) in photosynthetic rates, stomatal conductance, and fresh or dry weight between the supplementary pulsed and continuous LED light. The pulsed light (30/15 min) produces a statistically significant increase (Anova, p= 7.15x10-5) in terms of leaf area compared to the continuous LED light, allowing a 25% reduction in the operating time of the lighting system without negatively affecting this parameter.